Poloidally resolved measurements of the perpendicular propagation velocity of density fluctuations in ASDEX Upgrade L-mode plasmas. (20th January 2021) - Höfler, K; Happel, T; Hennequin, P; Stroth, U; Cavedon, M; Dux, R; Fischer, R; McDermott, R M; Poli, E; Schuster, C U; Wolfrum, E; Upgrade Team, the ASDEX
Abstract: Poloidal asymmetries of the propagation velocity of density fluctuations perpendicular to the magnetic field measured with Doppler reflectometry have been reported in several magnetic confinement plasma devices. Careful analysis of a large variety of different low confinement mode plasma scenarios performed at the ASDEX Upgrade tokamak does not reveal such an asymmetry outside the uncertainties of the evaluation process of the measurement data. The perpendicular velocity is investigated between mid-radius and the plasma edge and follows the poloidal dependence of the E × B drift velocity regardless of the probed turbulence structure size. Compared to measurements of a charge exchange recombination spectroscopy diagnostic this points towards a significantly smaller phase velocity than the E × B drift velocity. The analysis technique is presented in a representative discharge together with a sensitivity study of the impact of density, magneto hydrodynamic equilibrium and diagnostic alignment on the interpretation of the measured Doppler shift using ray tracing and thus on poloidal asymmetries. Three more highly different plasma scenarios with poloidally symmetric velocity profiles are shown.